Circulating secretory component in relation to early diagnosis and treatment of liver metastasis from colorectal carcinomas. - Kvale, D. (1992)
AIMS: To evaluate serum secretory component in relation to early detection and clinical management of liver metastasis in patients with colorectal cancer. METHODS: Secretory component and carcinoembryonic antigen (CEA) were analysed in serial serum samples from 23 patients who had liver metastases as the only apparent recurrence, and in sera from 54 matched controls. Results of surgical treatment of recurrences were classified peroperatively as radical when no residual tumour was apparent and resection margins were free of disease. RESULTS: In total, 18 (78%) patients had increased secretory component during the whole follow up period (median 16 months); 12 (52%) had raised secretory component concentrations before clinical recurrence (median lead time 5.2 months). There was no difference before recurrence between circulating secretory component and CEA in sensitivity and lead times. Seventeen patients underwent surgery for hepatic metastasis; seven had radical hepatic resection of which only two (29%) showed increased secretory component concentrations before clinical recurrence; both had concurrent raised CEA values. By contrast, secretory component was raised in 83% of those cases considered inoperable. CONCLUSIONS: Although serum secretory component clearly increases in most patients with liver metastases, its clinical value seems questionable because secretory component apparently indicates mainly inoperable hepatic metastases.